Partisipasi Siswa dalam Program Sekolah Adiwiyata SMA N 11 Semarang - Sugiarti, Laras Sih; Suroso, Suroso (Edu Geography, 2018)
The purpose of this research is to find out how the participation of students in the school program adiwiyata. The population in this study i.e., high school student N 11. The sample in this study i.e., students who are found at the time of research. The variable in this study i.e. students participation in following school programs adiwiyata. Data collection techniques using t question form and documentation. Analytical techniques descriptive test data using the percentage. The results showed that the participation of the students in the activities program of the school adiwiyata high school N 11 Semarang includes categories often. Students follow the activities into school programs adiwiyata in high school N 11 Semarang properly. Students follow the appropriate procedures or activities of an existing rule to complete the activity. The average student giving participation in any activity that is made by the school to achieve the goals of the school. Tujuan penelitian ini adalah untuk mengetahui bagaimana partisipasi siswa dalam program sekolah adiwiyata. Populasi dalam penelitian ini yaitu siswa SMAN 11 Semarang. Sampel dalam penelitian ini yaitu siswa yang dijumpai pada saat penelitian. Variabel dalam penelitian ini yaitu partisipasi siswa dalam mengikuti program sekolah adiwiyata. Teknik pengumpulan data menggunakan t angket dan dokumentasi. Teknik analisis data menggunakan uji deskriptif persentase. Hasil penelitian menunjukkan bahwa partisipasi siswa dalam kegiatan program sekolah adiwiyata di SMAN 11 Semarang termasuk kategori sering. Siswa mengikuti kegiatan yang menjadi program sekolah adiwiyata di SMA N 11 Semarang dengan baik. Siswa mengikuti kegiatan sesuai prosedur atau aturan yang ada sampai selesai kegiatan. Rata-rata siswa memberikan partisipasi dalam setiap kegiatan yang dibuat oleh sekolah untuk mencapai tujuan sekolah.